A framework for integrating the terrestrial carbon stock of estates in institutional carbon management plans. (19th November 2021) - Wang, Jiaqian; Werner, David; Manning, David A. C.
Abstract: Many institutions have substantial landholdings, but few consider soil carbon preservation and augmentation in their carbon management plans. A methodical framework was developed to analyse terrestrial carbon stocks (soil and tree biomass) for credible carbon offsetting strategies in institutional land. This approach was demonstrated at two farms (805 hectares) managed by Newcastle University. Soil carbon for three depths (0–30 cm, 30–60 cm and 60–90 cm) and above‐ground tree biomass were quantified. These data provided a terrestrial carbon baseline to evaluate future land management options and effects. Historical land‐use records enabled the following comparisons: (1) agricultural land vs. woodland; (2) arable land vs. permanent grassland; (3) organic vs. conventional farming; (4) coniferous vs. broadleaved woodland; and (5) recent vs. long‐established woodland. Carbon storage (kg/m 2 ) varied with land usage and woodland type and age, but only agricultural land vs. woodland, and for agriculture, arable land vs. permanent grassland, significantly affected the 0–90 cm soil carbon. At the university‐managed farms, current terrestrial carbon stocks were 103, 620 tonnes in total (98, 050 tonnes from the 0–90 cm soil and 5, 569 tonnes from tree biomass). These terrestrial carbon stocks were equivalent to sixteen years of the current carbon emissions of Newcastle University (6, 406 tonnes CO2  equivalents‐C per year). Using strategies for alternative land management, Newcastle University could over 40 years offset up to 3, 221 tonnes of carbon per year, or 50% of its carbon emissions at the current rate. The methodological framework developed in this study will enable institutions having large landholdings to rationally consider their estates in future soil carbon management schemes.